Equal Rights of Men and Women in the Current and Draft Civil Code - Marcenaro Frers, Ricardo (1983)
The most deeply rooted and difficult to eradicate expression of control and domination is the supremacy that men have historically exercised over women, proving to be a dynamic of unequal power that has endured over time. Consequently, its incidence is observed in the regulation of the Peruvian Civil Code. Given this situation, the paper recognizes that the most significant constitutional reform was to enshrine the equality of all persons before the law, who should enjoy the same rights and have identical obligations. Along these lines, women are no longer considered as subjects with relative incapacity and, in addition, they are granted the right to vote without restrictions. Likewise, the draft Civil Code incorporates a series of favorable reforms to the existing rules of cohabitation that only favored men. However, it’s also pointed out that, although a more equitable approach is promoted legislatively, this doesn’t imply that the Peruvian population is willing to change, and a cultural diffusion of equality between men and women is necessary.